Mean Daily Temperature Estimations and the Impact on Climatological Applications - Charalampos Kolyvas; Spyros Missiakoulis; Flora Gofa (Environmental Sciences Proceedings, 2023)
Climate variation in temperature describes the fluctuations that occur above or below the average temperature over time. This study focuses on the analysis of various approaches for calculating the average temperature to better capture and represent the true average temperature over the course of a day. As the conventional approach often fails to integrate significant behaviors of temperature variations, nine mathematical formulas are employed with a different number of daily observations. Specifically, this study inserts the geometric and harmonic mean and their variations for the estimation of the average temperature. Furthermore, the application of the formulas to the time series of temperature recordings for three station locations in Greece is analyzed. For the evaluation of the results, six widely used statistical indices for quantifying errors are applied, and their relative effects are also discussed. Finally, as a practical application of the impact of the formula used for the averaging of daily temperature, the various approaches are introduced on the same observation dataset for the estimation of the heating degree-days, an index that can have significant climatological and economic implications over a region.